A comprehensive taxonomic list of brittle stars (Echinodermata: Ophiuroidea) from submarine caves of the Ryukyu Islands, southwestern Japan, with a description of a rare species, Dougaloplus echinatus (Amphiuridae) - Okanishi, Masanori; Fujita, Yoshihisa (Zootaxa, 2019)
The ophiuroid species listed were collected by benthic faunal surveys from 2016 to 2018 in submarine caves of the Ryukyu Islands, southwestern Japan. The material includes 20 species from 8 families, Amphiuridae, Ophiocomidae, Ophiodermatidae, Ophiolepididae, Ophioleucidae, Ophiomyxidae, Ophionereididae and Ophiotrichidae. This is the first comprehensive report of submarine cave-dwelling ophiuroids from Japanese waters. Also provided is a redescription of a rare species, Dougaloplus echinatus (Ljungman, 1867), with a detailed description of its ossicle morphology. The species has previously been reported from Brazil, Australia, Eastern Indian Ocean to Southern China, in 11–118 m depth, and this is the first record of D. echinatus from Japanese waters. A brief discussion of the scarcity of submarine cave systems, and the need for their conservation, is provided.